2020
DOI: 10.1101/2020.07.14.20154005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A sensitive and affordable multiplex RT-qPCR assay for SARS-CoV-2 detection

Abstract: With the ongoing COVID-19 pandemic, caused by the novel coronavirus SARS-CoV-2, there is need for sensitive, specific and affordable diagnostic tests to identify infected individuals, not all of whom are symptomatic. The most sensitive test involves the detection of viral RNA using RT-qPCR, with many commercial kits now available for this purpose. However, these are expensive and supply of such kits in sufficient numbers cannot always be guaranteed. We therefore developed a multiplex assay using well-establish… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…Group tests in University halls of residence, labs or departments could likewise enable safer in-person interaction. There is exciting potential for combining group testing with cheaper multiplex RT-PCR tests (see, e.g., 19 ) for the purposes of population screening. The combination may yield cost reductions of over two orders of magnitude.…”
Section: A C C E L E R a T E D A R T I C L E P R E V I E Wmentioning
confidence: 99%
“…Group tests in University halls of residence, labs or departments could likewise enable safer in-person interaction. There is exciting potential for combining group testing with cheaper multiplex RT-PCR tests (see, e.g., 19 ) for the purposes of population screening. The combination may yield cost reductions of over two orders of magnitude.…”
Section: A C C E L E R a T E D A R T I C L E P R E V I E Wmentioning
confidence: 99%
“…Real-time quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) was performed using the TaqPath™ Covid-19 RT-PCR Kit (A48067; ThermoFisher Scienti c™, Massachusetts, USA), a fast, highly sensitive, multiplex and robust RT-qPCR assay for the detection of SARS-CoV-2 23 . Nucleic acids were isolated according to manufacturer's instructions.…”
Section: Pcr Test For Viral Detectionmentioning
confidence: 99%
“…Compared to MERS-CoV-2, there are more studies which had described the use of qRT-PCR and qPCR in confirming the diagnosis of SARS-CoV-2 ( Table 2 ) [66] , [67] , [68] , [69] , [70] , [71] . Some studies had described the use of a single target like N gene to detect the presence of SARS-CoV-2 and such qRT-PCR test could detect around 5 RNA copies per reaction with a sensitivity of above 99% and specificity of 100% [71] , [72] .…”
Section: Different Diagnostic Approaches To Detect Mers-cov and Sars-cov-2 Infectionsmentioning
confidence: 99%
“…However, a group of Chinese scientists had reported that the limit of detection of qRT-PCR that targets both N and ORF 1ab could be as low as 1-10 RNA copies per reaction [75] and this implied that the test sensitivities could vary between different research groups and experimental conditions [73] , [74] , [75] . On contrary, three research groups had employed three SARS-CoV-2 targets that include N, E, and RdRp in their qPCR testings, and the test sensitivities were varied between different published reports but the test specificities were quite consistent (100%) between the three published findings [70] , [72] , [76] . Compared to N and E genes, the detection of RdRp could be at least 20-folds less sensitive and this suggested that both N and E genes should be selected to be used in the qPCR test to confirm SARS-CoV-2 infection, followed by RdRp [70] .…”
Section: Different Diagnostic Approaches To Detect Mers-cov and Sars-cov-2 Infectionsmentioning
confidence: 99%